PEMANFAATAN WEBSITE DALAM SISTEM INFORMASI PERSEDIAAN BAHAN BAKU (STUDI KASUS : PT. ADI KARYA GEMILANG WAY KANAN) - Eva Itmaana; suparmono suparmono (Jurnal Alih Teknologi Sistem Informasi (JATSI), 2021)
PT. Adi Karya Gemilang Way Kanan is a company engaged in the processing of produktion many activities such as production an sales. In produktion activities will do finitely reguire raw materials to be produced after the raw material in production it will produce goods to be ready selling. Observation system lossmeans that studying the existing problems in the rightway PT. Adi Karya Gemilang magnificent work such as material inventory system the standard way of processing still use manual and time consuming. PT. Adi Karya Gemilng scintillating master piece was founded in 1980 and head guarteredin way kanan located in Bandar Jaya, PT. Adi Karya Gemilang Way Kanan scintillating resounding have much in creace foreign exchange by always being pengespor ford pockaging, especially averseas frutt jepang. Keywords : Supply of rawmaterials